Exploring Derivatives by Means of GeoGebra - Sari, Puspita; Hadiyan, Aris; Antari, Dwi (Universitas Ahmad Dahlan, 2018)
The paper aims to explain how GeoGebra can be used in a differential calculus course to explore the Derivative concepts by providing dynamic-visualizations of the concept. Design research methodology was used in this research by designing an instructional design (hypothetical learning trajectories) in the first phase and conducting the teaching experiment in the second phase. The data collected during the experiment consist of video recordings of the classroom activities, observations, interviews, and students written work. In the third phase of the design research, the data were analyzed retrospectively by comparing the actual learning process and the hypothetical learning trajectory. The results show that the dynamic feature of GeoGebra offers the possibility of zooming in on a graph corresponds to taking infinitesimal when a secant line transforms into a tangent line. This builds a foundation for the understanding of the definition of derivative intuitively.